Performance measurement in public sector organizations focus on local governments - Esden, Bootes P. (2001)
Performance Measurement is seen as a very important component of new public management (NPM). But measuring performance in the public sector has always been said to be difficult. This paper argues that performance measurement in public sector organizations may be difficult but not impossible. It aims to discuss the basics of performance measurement in organizations and explore the difficulties accompanying its implementation in public sector organizations (PSOs). Possible solutions will then be looked at, citing relevant experiences of PSOs, especially local governments, which are actually engaged in performance measurement and how they have overcome the difficulties that come with it. Afterwards, the paper will look at the Philippine case and see what is being done in the direction of utilizing performance measures in Philippine PSOs, most specifically in local government units (LGUs), analyze it and then come up with recommendations for Philippine LGUs' use.
Keywords: Performance evaluation; New Public Management (NPM); Public sector